Institutionalization of organizational change outcomes in development cooperation projects: The mediating role of internal stakeholder change-related beliefs - Andrew Ronnie Mugenyi; Charles Karemera; Joshua Wesana; Michaël Dooms (Administrative Sciences, 2022)
This paper investigated how change outcomes of development cooperation projects can be institutionalized within the beneficiary organization. While a lot of attention has been paid to sustainability in scientific research on issues, projects, and policies related to environmental, industrial, and agricultural production and sustainability management, there are limited studies on the sustainability of organizational-level change outcomes of aid-based project interventions. Using the lens of organizational change institutionalization models, we examined how internal stakeholders' change-related beliefs, organizational characteristics, and project characteristics relate to the institutionalization process of project outcomes. Data were collected using a questionnaire returned by 130 respondents from a university in the Global South implementing institutional development cooperation projects. Using partial least squares structural equation modeling (PLS-SEM) to analyze the data, we found that organizational characteristics and change-related beliefs both had direct positive effects on the institutionalization process, while project characteristics had negative effects. Additionally, this study reveals that stakeholder change-related beliefs mediated the relationship between organizational and project characteristics and the institutionalization process. The findings support the continual engagement of organizational internal stakeholders in institutionalization efforts throughout the project life cycle, rather than waiting for the project to end. In contrast to the mechanistic, linear result chain approaches that dominate development project discourses, there is a need for more iterative approaches that allow the development of necessary attitudes and behaviors among the beneficiary organization's internal stakeholders to sustain the project-induced changes.
Keywords: 350; change-related beliefs; change institutionalization; internal stakeholders; organizational characteristics; project characteristics; development cooperation projects